NUMERICAL MODAL ANALYSIS OF DOUBLE ARC GEAR - ZHANG Lan (Jixie qiangdu, 2016)
Double arc gears are widely used in high load speed reducers,and the inherent mode has an important influence on the performance of the reducer. Computational modal analysis is an efficient method for modal analysis of components using finite element software. In this paper,the modal analysis of the double arc gear was carried out using ABAQUS / CAE software,and discussed the gear in the gear spiral angle on the impact of modal. It will provide basis for dynamic performance optimization,vibration fault analysis and prediction.